Accumulation des stocks de carbone dans les sols sous des cultures bioénergétiques de Populus spp., Salix spp. et Panicum Virgatum - Martine Routhier; Benoit Lafleur; Nicolas Bélanger (VertigO)
Globally, soils contain about 2000 Gt of carbon (C). Over the past centuries, however, land use has contributed to the release of about 140 Gt of C to the atmosphere. Nonetheless, the establishment of crops on marginal lands could reduce atmospheric C by accumulating it in soils. This study aimed to identify the effects of soil texture, land use history and time following cultivation on soil C accumulation since the establishment of two woody species (Populus spp. , and Salix spp. ) and one herbaceous species (Panic virgatum). Overall, over relatively short periods of time (less than 20 years), our results indicate that these cultures accumulate a considerable amount of soil organic carbon (SOC) compared to previous land uses. Under woody species and P. virgatum, sites with clay content >20 % had SOC stocks 10-20 % higher than control sites, whereas this difference was approximately 5 % for crops with soil clay content